2018
DOI: 10.1080/02656736.2018.1516301
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging features influencing high-intensity focused ultrasound ablation of adenomyosis with a nonperfused volume ratio of ≥90% as a measure of clinical treatment success: retrospective multivariate analysis

Abstract: View related articles View Crossmark data Citing articles: 1 View citing articles Magnetic resonance imaging features influencing high-intensity focused ultrasound ablation of adenomyosis with a nonperfused volume ratio of !90% as a measure of clinical treatment success: retrospective multivariate analysis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 39 publications
4
30
0
Order By: Relevance
“…Multivariate logistic regression analysis also confirmed that patients with diffuse adenomyosis had lower pregnancy rates after HIFU treatment (Table 7). This result is consistent with that of a previous study, which showed that diffused lesions required larger ablation areas, leading to more severe burning of the uterine endometrium, and a reduced non-perfused volume [38].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Multivariate logistic regression analysis also confirmed that patients with diffuse adenomyosis had lower pregnancy rates after HIFU treatment (Table 7). This result is consistent with that of a previous study, which showed that diffused lesions required larger ablation areas, leading to more severe burning of the uterine endometrium, and a reduced non-perfused volume [38].…”
Section: Discussionsupporting
confidence: 93%
“…Of the 50 patients, 8 (16%) were diagnosed with primary infertility, and 42 (84%) were diagnosed with secondary infertility. In the LE group, the average age of patients was 35 years (IQR [31][32][33][34][35][36][37][38]. Before LE treatment, their average uterine volume was 148.3 cm 3 (IQR 73.5-202.1).…”
Section: Patients' Characteristicsmentioning
confidence: 99%
“…In addition, some patients are refractory to drug therapy. Although high intensity focused ultrasound (HIFU) and uterine arterial embolization (UAE) are both effective in the treatment of adenomyosis, yet, the therapeutic effects of these two techniques on adenomyosis still remain to be further investigated 1216. As a matter of fact, only total hysterectomy can thoroughly treat adenomyosis.…”
Section: Introductionmentioning
confidence: 99%
“…The calculate of Uterine volume used a formula based on an ellipsoid shape: L×W×AP diameter×0.52 [18]. the focal AM volume(v): v=1/6 π×a×b×c, and a, b, and c are diameters measured in orthogonal planes on T2W images [19]. The calculate of focal AM lesion ratio was focal AM lesion size/ uterine volume.…”
Section: Mri Protocolsmentioning
confidence: 99%